1969
DOI: 10.2136/sssaj1969.03615995003300010031x
|View full text |Cite
|
Sign up to set email alerts
|

Clay Mineralogy of Soils Formed on Mazama Pumice

Abstract: Amorphous components predominated in the clay size fraction of samples taken across a climatic transect of soils from Mazama pumice in central Oregon. The amounts were greatest in the less intensely weathered horizons, i.e., in lower horizons and at drier sites of the transect. Crystalline minerals were present in relatively small percentages and were unexpectedly complex. The phyllosilicates included beidellite, montmorillonite, vermiculite, a micaceous component, chloritic intergrades, and chlorite. Non‐phyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1973
1973
2009
2009

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…It is now recognized that seven different specimen pretreatments (Chichester et al 1969;McKeague 1978) (Srodon 1980 (Dudas and Pawluk 1976 (Fig. I a, b).…”
mentioning
confidence: 99%
“…It is now recognized that seven different specimen pretreatments (Chichester et al 1969;McKeague 1978) (Srodon 1980 (Dudas and Pawluk 1976 (Fig. I a, b).…”
mentioning
confidence: 99%
“…Smectite has also been identified as a major clay component of soils formed in Holocene tephra in the Pacific Northwest region. Chichester et al (1969) found clay-size fractions of soils formed on Mazama pumice in Oregon to be dominated by amorphous components, but reported beidellite as a constituent of crystalline clay fractions. Similarly, Dudas and Harward (1975) identified beidellite as a major component of the crystalline coarse clay fractions of soils derived from Mazama ash.…”
Section: Introductionmentioning
confidence: 94%
“…Beidellite was reported in clay fractions of non-podzolized soils formed in Mazama tephra, but only in samples that were treated with boiling KOH and acid a m m o n i u m oxalate prior to X R D analysis (Chichester et al 1969). Because hydroxy-interlayered 2:1 clays were the dominant layer silicates in these clay fractions, this treatment undoubtedly resuited in at least some removal of hydroxy interlayers (Barnhisel and Bertsch 1989).…”
Section: Origin Of Beidellitementioning
confidence: 99%
“…In contrast to the little-weathered, well-crystallized chlorite and mica are the terrestrial weathering products, halloysite, kaolinite, vermiculite, and ML micamontmorillonite. These minerals, along with other kinds of intermediate mixed-layer clays, have been reported forming in soils of western Oregon (Robertson, 1963;Tidball, 1965;Chichester et al, 1969), mainly as weathering products of widespread, late Cenozoic volcanic ash, pumice, obsidian, lava flows, and cinder beds. But also, these various clays could form by weathering of plutonic rocks, metamorphosed sedimentary and volcanic rocks, and unmetamorphosed detrital rocks.…”
Section: Origin Of Clay Mineralsmentioning
confidence: 99%
“…Chichester et al, 1969); and 4) Halmyrolysis of volcanic material and montmorillonite, a process demonstrated by Rex (1967) the parent material may be from oceanic volcanic activity, or it may be carried to the sea from terrestrial sources by winds and streams.…”
Section: Late Pleistocene and Holocene Clay Mineral Compositions Oregmentioning
confidence: 99%